Mastering JavaScript design patterns discover how to use JavaScript design patterns to create powerful applications with reliable and maintainable code - Timms, Simon (Packt Publishing, 2014)
Annotation
Includes index. - Online resource; title from PDF title page (EBSCO, viewed May 14, 2015)
Keywords: JavaScript (Computer program language); Software patterns; Computer software -- Reusability; Scripting languages (Computer science); JavaScript (Langage de programmation); Logiciels; Modèles de conception; Logiciels; Réutilisation; Langages de script (Informatique); COMPUTERS; Programming Languages; JavaScript; Computer software; Reusability